Fistulae involving the appendix: a systematic review of the literature. Issue 10 (13th October 2020) - McDonald, Stephen J.; Lee, Felix; Dean, Nicholas; Ridley, Lloyd J.; Stewart, Peter
Abstract: Background: The appendix has a unique place in surgical history. Although the first ever appendicectomy involved a fistula to the skin, fistulae involving the appendix remain uncommon and can lead to unique surgical considerations. Methods: A systematic review of the literature was performed for case reports of appendiceal fistulae. We excluded cases in which the patient had a history of appendicectomy. Cases were categorized by site and aetiology, with information regarding relative frequency and demographics obtained. Results: A total of 301 case reports of fistula involving the appendix were found. The most common sites of these fistulae were to the bladder (148 cases), skin (40 cases), vasculature (19 cases), umbilicus (16 cases) and to the gastrointestinal tract. The most common aetiology in sub‐analysis was appendicitis alone (150 cases), with less common causes including appendiceal adenocarcinoma (32 cases) and congenital abnormalities (18 cases). There were significantly more appendiceal fistulae in males than in females, with a ratio of 1.7:1. In patients with appendiceal adenocarcinoma as a cause for fistula, there were significantly more females than males with a ratio of 2.3:1. Conclusion: In conducting a systematic review of case reports of fistulae involving the appendix, we identified 301 unique case reports, with a range of different sites and aetiologies. Abstract : We have conducted a systematic review of case reports of fistulae involving the appendix and identified 301 unique case reports, with a range of different sites and aetiologies.